Changes in prefrontal and amygdala activity during olanzapine treatment in schizophrenia - Blasi, Giuseppe (2009)
Earlier imaging studies in schizophrenia have reported abnormal amygdala and prefrontal cortex activity during emotion processing. We investigated with functional magnetic resonance imaging (fMRI) during emotion processing changes in activity of the amygdala and of prefrontal cortex in patients with schizophrenia during 8 weeks of olanzapine treatment. Twelve previously drug-free/naive patients with schizophrenia were treated with olanzapine for 8 weeks and underwent two fMRI scans after 4 and 8 weeks of treatment during implicit and explicit emotional processing. Twelve healthy subjects were also scanned twice to control for potential repetition effects. Results showed a diagnosis by time interaction in left amygdala and a diagnosis by time by task interaction in right ventrolateral prefrontal cortex. In particular, activity in left amygdala was greater in patients than in controls at the first scan during both explicit and implicit processing, while it was lower in patients at the second relative to the first scan. Furthermore, during implicit processing, right ventrolateral prefrontal cortex activity was lower in patients than controls at the first scan, while it was greater in patients at the second relative to the first scan. These results suggest that longitudinal treatment with olanzapine may be associated with specific changes in activity of the amygdala and prefrontal cortex during emotional processing in schizophrenia.